The silver eyes - Cawthon, Scott 1971-; Breed-Wrisley, Kira (Cawthon, Scott 1971- Five nights at Freddy's, 2016)
Ten years after the murders at Freddy Fazbear's Pizza, Charlie and her childhood friends get together on the anniversary of the event at the abandoned pizza place to find that the four animatronic entertainment mascots have changed.